POTENSI TEPUNG DAUN SIRSAK, SERAI, KENIKIR, JERUK NIPIS, DAN KLUWIH TERHADAP KUMBANG BUBUK KEDELAI (Callosobruchus analis F.) PADA KEDELAI (Glyxine max L.) DALAM SIMPANAN - Laily Dwi Dzulhijja; Wagiyana Wagiyana; Sigit Prastowo (Jember University Press, 2019)
ABSTRACT This study aims to determine the effect of soursop leaf flour, lemongrass flour, kenikir leaf flour, lime leaf flour, and kluwih leaf flour on: 1) mortality, 2) damage to seeds, 3) shrinkage of seed weight, 4) appearance of adult C. analysts on soybean seeds in deposits and 5) laying eggs of C. imago female eggs, 6) probit analysis LT50. The experiment was carried out using a Completely Randomized Design (CRD). As treatments are: A) controls; B) soursop leaf flour in doses of 1gr, 2gr, and 3gr; C) Serai leaf flour with doses of 1gr, 2gr, and 3gr; D) kenikir leaf flour with doses of 1gr, 2gr, and 3gr; E) lime leaf flour with doses of 1gr, 2gr, and 3gr; and F) kluwih leaf flour with doses of 1gr, 2gr, and 3gr. Each treatment uses five replications. The observed parameters were analyzed by